ANALYSIS OF THE INTERACTION OF ARTIFICIAL INTELLIGENCE AND BUSINESS ANALYTICS - Gusmanova Ф.Р.; Abdulkarimova Г.А.; Dalbekova К.С.; Berkimbaeva С.Б.; Kenzhegulova С.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Currently, integration with artificial intelligence tools has become a priority in the development of Business Intelligence systems (BI solutions), which has expanded the capabilities of BI systems with machine learning algorithms. BI system tools are part of the system work with data (business intelligence) that many enterprises use to make decisions. The interaction of artificial intelligence and business intelligence has enabled advanced real-time data analytics. BI system developers try to take into account the different needs of users, so they develop different approaches. The paper also discusses business intelligence tools - this is part of the data management system that many enterprises use to make decisions. The goal of the article is to analyze the possibilities of using artificial intelligence in Business Intelligence systems and describe various approaches to integrating AI algorithms into a BI system.